2016
DOI: 10.1016/j.ijsu.2016.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported adverse events after hernia surgery and socio-economic status: A register-based cohort study

Abstract: We detected inequalities related to income level, gender and ethnic background. Even if healthcare utilization is influenced by socio-economic background, careful information of what may be expected in the postoperative period and how adverse events should be managed could lead to reduced disparity and improved quality of care in the community at large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“… 6 , 8 , 9 However, a qualitative study from Sweden, a country with universal health care, showed no association between lower SES and worse outcomes of inguinal hernia repair. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 6 , 8 , 9 However, a qualitative study from Sweden, a country with universal health care, showed no association between lower SES and worse outcomes of inguinal hernia repair. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors have been shown to be associated with stoma reversal rate [ 15 , 17 , 18 ]. Income, education and occupation are well-known variables used for classification of socioeconomic status [ 19 , 20 ]. Kuryba et al [ 15 ] evaluated factors affecting stoma reversal rate in 4879 rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…When adverse events were studied later, and merged data from the SHR with data from the national patient register, the male gender was found to be associated with an increased risk of both cardiovascular events and intraoperative complications [ 21 ]. A study from 2002 found that although women had neither more registered nor more self-perceived adverse events, they sought healthcare advice regarding their perceived complications more often (in 75% of cases versus 48% for men, p = 0.003) in a study cohort from 2002 [ 22 ]. A tendency, although not statistically significant, for women to file damage claims more often (OR 1.62, 95% CI 0.98–2.71, p = 0.06) after groin hernia surgery was found by Nordin et al, while they were investigating damage claims between 2008 and 2010 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%